An Imperative Duty - Howells, William Dean (Broadview Press, 2010)
Keywords: Fiction; Fiction; Passing (Identity); Fiction; Young women; Racially mixed people; dept.eng; faculty_collection

Ruthless: Poems - Mock, Jeff (Three Candles Press, 2010)
Keywords: dept.eng; faculty_collection

Blood and Bravery: Voices of Biafran Veterans of the Nigeria-Biafra War - Ogbaa, Kalu (Sungai, 2010)
Keywords: Civil War; 1967-1970; History; Nigeria; dept.eng; faculty_collection

All of Your Messages Have Been Erased - Shipley, Vivian (Louisiana Literature Press, 2010)
Keywords: dept.eng; faculty_collection

Freud as new woman writer: Maternal ambivalence in Studies on Hysteria - Fluhr, N. (English Literature in Transition, 1880-1920, 2010)
Keywords: dept.eng; ⛔ No DOI found

Woolf’s editorial self-censorship and risk-taking in Jacob’s room - Neverow, V. (Virginia Woolf and the Literary Marketplace, 2010)
Journal Abbreviation: Va. Woolf and the Literary Marketpl.
Keywords: dept.eng

Virginia Woolf and city Aesthetics - Neverow, V.S. (The Edinburgh Companion to Virginia Woolf and the Arts, 2010)
Journal Abbreviation: The Edinburgh Companion to Virginia Woolf and the Arts
Keywords: dept.eng

Latin Alive: The survival of Latin in English and the Romance languages - Solodow, J.B. (Cambridge University Press, 2010)
In Latin Alive, Joseph Solodow tells the story of how Latin developed into modern French, Spanish, and Italian, and deeply affected English as well. Offering a gripping narrative of language change, Solodow charts Latin's course from classical times to the modern era, with focus on the first millennium of the Common Era. Though the Romance languages evolved directly from Latin, Solodow shows how every important feature of Latin's evolution is also reflected in English. His story includes scores of intriguing etymologies, along with many concrete examples of texts, studies, scholars, anecdotes, and historical events; observations on language; and more. Written with crystalline clarity, this is the first book to tell the story of the Romance languages for the general reader and to illustrate so amply Latin's many-sided survival in English as well. © Joseph B. Solodow 2010.
Journal Abbreviation: Latin Alive: The Survival of Latin in Engl. and the Roman. Languages Pages: 356 Publication Title: Latin Alive: The Survival of Latin in Engl. and the Roman. Languages
Keywords: History; History; Latin language; Influence on English; Romance languages; Influence on Romance; Latin language; Latin language; dept.eng; faculty_collection

Guenevere: the abbess of amesbury and the mark of reparation - Holbrook, Sue Ellen (Arthuriana, 2010)
Malory elevates Guenevere to abbess ofAmesbury where she heals her soul through a penitential process clarified by Cassian's teachings on attitude and supplication and by the cloister context and devotional formulas of her speech on salvation. (SEH).
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/102-712-156-403-804 tex.type: [object Object]
Keywords: dept.eng